Migrants' digital knowledge flows: How digital transformation shapes social behaviour - Alexandra David; Judith Terstriep; Paolo Sospiro; Elisa Scibè (Institut Arbeit und Technik (IAT), 2019)
* From a macro-perspective, digital transformation regarded as a continuous process not only impacts our daily lives but also influences social phenomena such as migration processes. * Rather than a luxury item, for refugees' smartphones appear to open a "new window" to the outside world, which influence social behaviour. * Digital, real-time knowledge and information exchange help refugees to find orientation on their escape routes and within the receiving country and thus, are likely to affect migration processes. * Digital apps and social media in particular are important information and communication channels, which accelerate the circulation of information. However, they might also contribute to the creation of positive and negative myths about destination countries.
Keywords: 330